OPERATIONAL AUDIT TO ASSESS THE EFFECTIVENESS OF NPK RAW MATERIAL INVENTORY MANAGEMENT (A CASE STUDY OF PT. PUPUK KALIMANTAN TIMUR) - Muhammad Azhar Rasyiid (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
PT. Pupuk Kalimantan Timur, as one of the biggest fertilizer companies in Indonesia,also contributes to the government's national food security program by increasing itsNPK fertilizer production from an original capacity of 350 thousand tons per year to 1million tons per year. The huge increase in production capacity led the researcher to findout how to manage NPK raw material inventory to meet the targets set by PT. PupukKalimantan Timur. This study aims to determine and assess the effectiveness of internalcontrol functions of NPK raw material inventory management in PT. Pupuk KalimantanTimur. This research is a qualitative research using the descriptive case study approachmethod. The data collection techniques in this study are conducting observations,conducting interviews, reviewing company procedures, and conducting literature studiesin relation to the research problem. The scope is focused on the function of raw materialinventory management, which includes the selection and planning of needs, procurement,acceptance, storage, control, distribution, and administration. The results of the studyshowed that the implementation of the function of raw material inventory management inPT. Pupuk Kalimantan Timur has been running effectively, but there are some issues thatstill need to be resolved. The researcher recommends improvements that can beconsidered by the company to improve the effectiveness of the company's operationalactivities, especially in managing NPK raw material supplies.Keywords: Operational Audit, Effectiveness, Inventory Management, Inventory Function,Raw Material Inventory